Penerapan Senam Ergonomis Terhadap Penurunan Kadar Asam Urat pada Lansia di Desa Pondok Sukoharjo - Salsabilla Firdausia; Mulyaningsih Mulyaningsih (Vitamin : Jurnal ilmu Kesehatan Umum, 2024)
Background: Gout is a disease associated with high levels of uric acid in the blood. Apart from the aging process, gout can also occur due to the inhibition of the secretion process and a decrease in the enzyme uricase. The aging process in the elderly causes various health problems, as a result of which they are susceptible to diseases, one of which is an increase in uric acid. Uric acid numbers can be said to be abnormal if >6 mg/dl for women and >7.2 mg/dl for men. Non-pharmacological therapy that can be done is ergonomic exercise. The purpose of this study is to compare measurements of uric acid levels before and after ergonomic exercise. Methods: A case study of 2 respondents was conducted three times a week, with a duration of 19 minutes for each exercise. Results: The application of the two respondents resulted in a significant decrease in uric acid levels; namely, Mrs. S obtained a result of 4.8 mg/dl, while Mrs. T obtained a result of 5 mg/dl. Conclusion: The results of this study concluded that there was a decrease in uric acid levels in both respondents after ergonomic gymnastics.